Seasonal Trends in Catches of Moths of the Tobacco Hornworm, Tomato Hornworm, and Corn Earworm in Traps Equipped with Blacklight Lamps in North Carolina. Issue 1 (24th September 2014) - Stewart, Paul A.; Gentry, Cecil R.; Knott, Crawford M.; Lam, Jesse J.
Abstract : Catches in traps equipped with blacklight lamps provided data for the construction of curves showing seasonal trends in the populations of moths of the tobacco hornworm, Manduca sexta (Johannson); tomato hornworm, M. quinquemaculata (Haworth); and corn earworm, Heliothis zea (Boddie). Both species of Manduca generally had 3 peaks of populations, the first sometime between mid-May and late June, the second from mid-July until late August, and the third in early or mid-September. The second peak was usually, but not always, much higher than the first, and the third was usually lowest. Populations were always low the first 2 weeks of July. Major changes in levels were abrupt and marked between successive weeks. In some years, relatively high levels were maintained as long as 6 weeks; in other years, they were maintained only 1 or 2 weeks. The catch of males was usually, but not always, higher than that of females. Seasonal curves for the 2 species of Manduca were generally similar. The population of H. zea was low until mid-August, when an abrupt increase resulted in the season's peak. Decline started the first week after the peak was reached and generally continued until the end of the trapping season. Minor increases sometimes occurred in late September.